2017
DOI: 10.3906/sag-1601-58
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of major and minor lower extremity amputation in diabetic foot patients

Abstract: Background/aim: We evaluated the existing risk factors with clinical results in patients who underwent major and minor amputation of the lower extremity as a result of diabetic foot ulcers (DFUs). Materials and methods: We retrospectively studied 107 patients who had undergone lower extremity amputation. The patients were divided into minor (Group 1, n = 75) and major (Group 2, n = 32) amputation groups. On clinical evaluation, the type of surgery performed, smoking history, comorbidities, duration of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
4
22
2
Order By: Relevance
“…We found that age was not a significant risk factor for amputation in patients with DFI. However, male sex and smoking, which were indicated as risk factors for amputation in diabetes‐related foot ulceration, were also found to be risk factors for amputation in DFI in our meta‐analysis. This may be because male sex and smoking have traditionally been the main factors in the development of PAD caused by atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We found that age was not a significant risk factor for amputation in patients with DFI. However, male sex and smoking, which were indicated as risk factors for amputation in diabetes‐related foot ulceration, were also found to be risk factors for amputation in DFI in our meta‐analysis. This may be because male sex and smoking have traditionally been the main factors in the development of PAD caused by atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 61%
“…Foot complications are common among elderly patients with diabetes . We found that age was not a significant risk factor for amputation in patients with DFI.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Diabetic foot ulcer (DFU) leading to lower extremity amputation (LEA) is one of the common complications of diabetes mellitus (DM) . DFUs are complex, chronic wounds, which have a major long‐term impact on the morbidity, mortality, physical distress, as well as financial losses that lower the quality of subjects' lives .…”
Section: Introductionmentioning
confidence: 99%
“…DM is a known systemic disease associated with increased incidence of morbidity and mortality. The treatment period of ulcers is long and poor treatment can lead to extremity amputations (3). Because of the amputation and mortality rate, diabetic foot receives more attention as a severe complication related to DM.…”
Section: Introductionmentioning
confidence: 99%